2018
DOI: 10.1016/j.chembiol.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of PTEN Modulation: Targeting Strategies from Gene to Protein

Abstract: Two decades have passed since the discovery of the tumor suppressor, PTEN. A multitude of biological functions have since been revealed, suggesting potential therapeutic applications for both PTEN activation (e.g., cancer) and inhibition (e.g., neuroregeneration). Nevertheless, PTEN's therapeutic suitability has been called into question due to its "risky" profile as a tumor suppressor. To evaluate PTEN function and its various roles in disease a number of molecules have so far been developed. However, intrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 148 publications
(161 reference statements)
0
41
0
1
Order By: Relevance
“…Regarding PTEN, therapeutic approaches aiming at restoring its activity to physiological levels are also pertinent. However, the multitude and high complexity of mechanisms (epigenetic, transcriptional, post‐transcriptional and post‐translational) regulating PTEN expression and activity have to date hindered the discovery of clinically relevant and selective PTEN modulators …”
Section: Discussionmentioning
confidence: 99%
“…Regarding PTEN, therapeutic approaches aiming at restoring its activity to physiological levels are also pertinent. However, the multitude and high complexity of mechanisms (epigenetic, transcriptional, post‐transcriptional and post‐translational) regulating PTEN expression and activity have to date hindered the discovery of clinically relevant and selective PTEN modulators …”
Section: Discussionmentioning
confidence: 99%
“…PTEN is a tumour suppressor of human cancer and has critical roles in the regulation of tumorigenesis and cell migration. Studies have shown that PTEN plays a crucial role in regulating the PI3K/Akt signalling pathway and that activation of Akt inhibits the autophagy pathway . Furthermore, PTEN has been reported to play a major role in inhibiting migration and invasion of tumour cell via the Akt/SP1/MMP2 pathway .…”
Section: Discussionmentioning
confidence: 99%
“…40 To detect whether miR-205 influences EPC migration by regulating F-actin filaments and MMP2, we performed way. 48,49 Furthermore, PTEN has been reported to play a major role in inhibiting migration and invasion of tumour cell via the Akt/SP1/ MMP2 pathway. 50 Intriguingly, autophagy inhibition promoted EPC migration by up-regulating MMP2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] RNAs are in constant dynamic interaction with other biomolecules such as proteins [5][6][7][8][9][10][11] and other RNAs (e.g.,s nRNAs,l ncRNAs, miRNAs), [12][13][14] thereby significantly altering cellular function and cell fate. [1][2][3][4] RNAs are in constant dynamic interaction with other biomolecules such as proteins [5][6][7][8][9][10][11] and other RNAs (e.g.,s nRNAs,l ncRNAs, miRNAs), [12][13][14] thereby significantly altering cellular function and cell fate.…”
Section: Introductionmentioning
confidence: 99%
“…RNAh as been recognized as am ajor player in cellular function for decades now; however,r obust methods to directly measure and understand the different functions of RNAi nc ells are still under development. [1][2][3][4] RNAs are in constant dynamic interaction with other biomolecules such as proteins [5][6][7][8][9][10][11] and other RNAs (e.g.,s nRNAs,l ncRNAs, miRNAs), [12][13][14] thereby significantly altering cellular function and cell fate. [15][16][17][18] State-of-the-art methods to detect an RNA of interest (ROI) and its cellular interactions include fluorescence in situ hybridization (FISH) [19,20] and the MS2-green fluorescent protein (MS2-GFP) system where the interaction between an RNAd erived from enterobacteria phage MS2 and the MS2 coat protein fused to GFP is used to detect an ROI.…”
Section: Introductionmentioning
confidence: 99%